Micron and nano hybrid ufasomes from conjugated linoleic acid, their vesiculation and encapsulation of ginsenoside Rg3. (21st January 2022) - Liu, Huan; Hu, Xueyi; Li, Lei; Meng, Xinyu; Fang, Yun; Xia, Yongmei
Abstract: BACKGROUND: Unsaturated fatty acids used to form unstable micro‐vesicles, while conjugate linoleic acid (CLA)‐sodium dodecyl sulfate (SDS) can self‐assembly to stable nano‐conjugate linoleic acid vesicles (nano‐CLAVs). Generally, micro‐capsule could geometrically provide higher loading capacity but also generate concerns in construction convenience, sustained release, bioaccessibility and stability. Hence there is a contradiction between loading capacity and encapsulation efficiency. Therefore, the study of the factors that decide the capsule size falling in nano or micron size with same capsule material would be a benefit to food or drug delivery science. RESULTS: The micron‐ and nano‐CLAVs were constructed for encapsulation and sustained release of ginsenoside Rg3. The formation mechanism of nano or micron capsule, s the effect of vesicle sizes on encapsulation efficiency, drug loading efficiency and stability of the encapsulated Rg3 were investigated. It was found that with the addition of salt (PBS), the size of CLAVs jumped from nano to micron. Furthermore, the salt concentration is the key factor that decides the vesicle size of nano or micron. The pH at fabrication triggers the vesiculation and dramatically affects the vesicle size over the nano and micron scales. CONCLUSION: Compared to the nano‐CLAVs, micron vesicles enhanced the loading capacity to 137.6% and the encapsulation efficiency to 138.4%, respectively. Meanwhile, the micron‐CLAVs performed similar sustained release of Rg3 as the nano‐CLAVs did, and was stable for 120 days at room temperature or sustained 98.9% of capsules after centrifuge at 6090 × g for 20 min. © 2022 Society of Chemical Industry.